Ocular findings in patients with systemic sclerosis (Clinics, 2011)
OBJECTIVE: To evaluate the frequency and characteristics of ocular manifestations in outpatients with systemic sclerosis. METHODS: In this cross-sectional study, 45 patients with systemic sclerosis were enrolled. Data regarding demographics, disease duration and subtype, age at diagnosis, nailfold capillaroscopic pattern and autoantibody profile were collected, and a full ophthalmic examination was conducted. Parametric (Student's t-test) and nonparametric (Mann-Whitney U test) tests were used to compare continuous variables. Fisher's exact test was used to compare categorical data. P values < 0.05 were considered significant. RESULTS: Twenty-three subjects (51.1%) had eyelid skin changes; 22 (48.9%) had keratoconjunctivitis sicca, 19 (42.2%) had cataracts, 13 (28.9%) had retinal microvascular abnormalities and 6 (13.3%) had glaucoma. Eyelid skin changes were more frequent in patients with the diffuse subtype of systemic sclerosis and were associated with a younger age and an earlier age at diagnosis. Cataracts were presumed to be age-related and secondary to corticosteroid treatment. There was no association between demographic, clinical or serological data and keratoconjunctivitis sicca. The retinal microvascular abnormalities were indistinguishable from those related to systemic hypertension and were associated with an older age and a severe capillaroscopic pattern. CONCLUSIONS: Eyelid skin abnormalities and keratoconjunctivitis sicca were the most common ocular findings related to systemic sclerosis. Some demographic and clinical data were associated with some ophthalmic features and not with others, showing that the ocular manifestations of systemic sclerosis are characterized by heterogeneity and reflect the differences in the implicated pathophysiological mechanisms.